PENGARUH CITRA MEREK DAN GAYA HIDUP TERHADAP KEPUTUSAN PEMBELIAN IPHONE PADA PEREMPUAN MILENIAL DI KOTA LANGSA - M Dody Haulussy; Rahmi Meutia; Maulana Rahman (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to analyze the effect of brand image, lifestyle, and price on iPhone purchasing decisions for millennial women in Langsa City. The sample in this study amounted to 96 respondents. The data analysis method uses multiple linear regression analysis, t test, F test and coefficient of determination test. The regression equation in this study is Y = 2.118 + 0.181X1 + 0.036X2. Brand image has a significant effect on purchasing decisions for Iphone for millennial women in Langsa City. Lifestyle has a significant effect on purchasing decisions for iPhones for millennial women in Langsa City. brand image and lifestyle simultaneously have a significant effect on iPhone purchasing decisions for millennial women in Langsa City. Based on the coefficient of determination test, it can be explained that the Adjusted R Square value is 0.521. This means that the Brand Image and Lifestyle variables on Purchasing Decisions are 52.1%, while the remaining 47.9% is influenced by other variables outside this research model.